The technology fix : the promise and reality of computers in our schools - Pflaum, William D., 1939- (Association for Supervision and Curriculum Development, 2004)
During the technology boom of the 1980s and 1990s, computers seemed set to revolutionize education. Do any of these promises sound familiar? . Technology would help all students learn better, thanks to multimedia programs capable of adapting to individual needs, learning styles, and skill levels. . Technology would transform the teacher's role from a purveyor of a one-size-fits-all curriculum to a facilitator of student exploration. . Technology would replace textbooks with dynamic, interactive learning resources that were always up-to-date. . Technology would boost test scores, as engaged and motivated students acquired advanced skills, problem-solving abilities, and a growing thirst for knowledge. By 2001, educational materials developer William D. Pflaum had begun to suspect that technology was not the all-purpose solution it had seemed. Deciding to see how computers were really being used in U.S. classrooms, he embarked on a yearlong road trip to a cross-section of schools throughout the nation. In this book, he recounts his journey. Although he did find technology application to admire, too often he found broken promises: millions spent for little measurable gain, problems instead of solutions, a fix instead of a fix. This inside look at computer use in our schools shares the voices, experiences, triumphs, and frustrations of educators and students in urban, rural, and suburban settings. The author provides insight into the key roles that computers play in the classroom and clarifies what we must do to ensure that the promise of technology is fulfilled ... and that students truly benefit.